On Teaching Computer Ethics within a Computer Science Department. - Quinn, Michael J. (Science & Engineering Ethics, 2006)
The author has surveyed a quarter of the accredited undergraduate computer science programs in the United States. More than half of these programs offer a "social and ethical implications of computing" course taught by a computer science faculty member, and there appears to be a trend toward teaching ethics classes within computer science departments. Although the decision to create an "in house" computer ethics course may sometimes be a pragmatic response to pressure from the accreditation agency, this paper argues that teaching ethics within a computer science department can provide students and faculty members with numerous benefits. The paper lists topics that can be covered in a computer ethics course and offers some practical suggestions for making the course successful.